Building meaningful partnerships: engaging and co-developing a patient advisory council to inform the implementation of person-centred quality indicators in Alberta primary care - Matthew Luzentales-Simpson; Ingrid Nielssen; Fakhriyya Aghabayli; Sadia Ahmed; Kalpana Thapa Bajgain; Ifrah Anjum; Veronika Kiryanova; Safa Ahmed; Kim Giroux; D’Arcy Duquette; Eleanor Benterud; Paul Fairie; et al. (Research Involvement and Engagement, 2026)
Abstract Background Effective primary care improves patient outcomes by providing comprehensive, continuous, and person-centred care. The Patient’s Medical Home vision positions primary care as the central entry point to high-quality health care in Canada. In Alberta, Person-centred Care Quality Indicators (PC-QIs) were developed with patients and health system stakeholders, are being implemented across the province to assess and report patient experiences in primary care. To ensure that patients are central to this work, a PC-QI patient Advisory Council (PAC) was created. Methods The PC-QI PAC was formed in 2024 to support the provincial implementation of PC-QIs in primary care. The council included ten total members, eight patient research partners and two academic researchers, who co-developed a living Terms of Reference to guide the PAC’s operations. Monthly PAC meetings (later adapted to quarterly meetings with monthly newsletters) and working group meetings supported engagement. The patient engagement was evaluated twice using the Patient Engagement in Research Scale. Results The PC-QI PAC contributed to the development of the Terms of Reference, research participant recruitment strategies, co-development of study materials, knowledge translation activities, and research dissemination. Members also co-authored abstracts, posters, and manuscripts, and participated in academic conferences and meetings. Key facilitators of engagement included the co-developed Terms of References, transparent communication, flexible participation in working groups, appropriate compensation, and leadership roles for patient co-chairs. Identified challenges included maintaining clarity of roles, sustaining engagement in virtual settings, and ensuring that members’ contributions to the broader project were clearly communicated and understood. Conclusion By managing expectations, co-developing operations, and thoughtfully sharing information, the research team built meaningful, trustworthy, and long-lasting partnerships with patient partners, which benefited every team member and the research project. This study aims to describe and analyze the co-development and work of the PC-QI PAC to identify factors that shape meaningful patient engagement in the design and implementation of research in primary care, contributing to the limited evidence on this topic.